“Does the topic require us to reconsider?” The (De)Legitimation of Inclusive Language - Shenk, Elaine M. (2025)
This article investigates personal perspectives regarding several inclusive language options in Spanish. An initial survey was conducted among 109 speakers of Spanish (L1, HL, L2) and of that group, 23 individuals participated in a deeper exploration of the topic by way of personal interviews and written questions. The study identifies the most commonly recognized strategies, personal usage patterns, and experiences related to using (or not using) inclusive language. The paper analyzes qualitatively three distinct themes that arose with some frequency among the participants, which are situated in a theoretical framework of linguistic legitimation: (1) prioritizing respect and inclusion in one’s discourse for women and non-binary individuals, despite the linguistic challenges; (2) rejecting inclusive language due to a valuation of aesthetic and grammatical aspects; and (3) a self- limitation for L2 speakers who avoid advocating for inclusive language, even when they choose to use it in their own speech.